UPAYA PENINGKATAN PENDAPATAN RUMAH TANGGA MELALUI PENGEMBANGAN USAHA PADA KELOMPOK PETERNAK IKAN DENGAN MENGGUNAKAN SISTEM BIOFLOK DI DESA TAWANGBANTENG KEC. SUKARATU KAB. TASIKMALAYA - Ai Siti Nurjamilah,; Welly Nores Kartadireja ,; Fikri Hakim,; Iis Aisyah, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
Household income is all income or receipts in the form of money or goods from all household members obtained, either in the form of wages/salaries, income from household businesses, other income, and income from gifts from other parties. In other words, household income is remuneration for labor production factors, remuneration for capital, as well as income derived from gifts from other parties. One of the sources of household income is livestock sector income. One way to increase household income is to develop a fish farmer group business using a biofloc system. In the village of Tawangbanteng, Sukaratu District, Tasikmalaya Regency, there is a group of fish farmers who need morel and material assistance, especially during this pandemic. The action taken is to provide knowledge about raising fish with a biofloc system as well as assistance that can provide solutions for farmers, namely the implementation of PbM-KP (Service for the Food Security Society). This service aims to increase the knowledge and understanding of fish farmer groups using the biofloc system. In addition, farmers are also given information about the system of selling or distributing livestock products, especially through online media. The method implemented in this PbM-KP activity is gradual guidance and the provision of material assistance that is considered necessary in developing the mushroom farmer group business.